2010
DOI: 10.1002/jbm.a.32799
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration by bioactive hybrid membrane containing FGF2 within rat calvarium

Abstract: This study examined the bone regeneration potential of a novel hybrid membrane consisting of collagen and nano-bioactive glass (nBG) incorporating basic fibroblast growth factor (FGF2) for use in guided bone regeneration. nBG was added to a reconstitution of collagen at a concentration of 30%, and the hybrid was formulated into a thin membrane. FGF2 (50 microg/ml) was adsorbed to the hybrid membrane. This level of FGF2 was found to be the optimal concentration to stimulate osteoblastic differentiation in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Indeed, enhanced bone regeneration in a critical sized defect was obtained when collagen membranes doped with nanosized bioactive glasses had bFGF incorporated into them. 69 This correlates with data presented in the current study whereby matrix mineralization after several weeks in culture is greater in hydrogels containing bFGF. bFGF is not the only growth factor that can produce improved osteogenic responses and significant benefits have also been reported for other growth factors, including CTGF, 67 platelet-derived growth factor, 70 insulin-like growth factor, 71 and BMP2 [72][73][74] when loaded into various types of scaffold.…”
supporting
confidence: 91%
“…Indeed, enhanced bone regeneration in a critical sized defect was obtained when collagen membranes doped with nanosized bioactive glasses had bFGF incorporated into them. 69 This correlates with data presented in the current study whereby matrix mineralization after several weeks in culture is greater in hydrogels containing bFGF. bFGF is not the only growth factor that can produce improved osteogenic responses and significant benefits have also been reported for other growth factors, including CTGF, 67 platelet-derived growth factor, 70 insulin-like growth factor, 71 and BMP2 [72][73][74] when loaded into various types of scaffold.…”
supporting
confidence: 91%
“…The reconstructed 3-D lCT images showed the 3-D structure of the porous scaffold and bone in-growth within the defect region. Bone regeneration hardly occurred in the negative control, suggesting a critical size bone defect [25][26][27]. On the other hand, in the scaffold sample new bone in-growth could not be clearly differentiated from the remaining material.…”
Section: In Vivo Pilot Studymentioning
confidence: 85%
“…Tissue engineered bone and clinical translation revealed the most abundant member utilised within bone tissue engineering strategies in vivo was FGF-2, also known as basic FGF (Hirata et al, 2013;Hong et al, 2010;Maehara et al, 2009;Shirakata et al, 2010).…”
Section: Fgfmentioning
confidence: 99%
“…Considering related fold increases in bone formation within large (1.3 to 3 fold Shirakata et al, 2010)) and small animals (1.1 to 16.4 fold (Goodman et al, 2003;Hong et al, 2010)), it is interesting to note that higher dosages correlated with greater fold increases (defects with highest fold increase included tibial fracture and calvarial defect respective to large and small animals). Evidently, data suggest positive correlation between FGF-2 treatment and bone formation, potentially due to induced vessel ingrowth and ossification at the defect site (Guo et al, 2006;Maehara et al, 2009 (Bland et al, 1995;Dunstan et al, 1999;Kelpke et al, 2004), and one study utilised FGF-18 (Carli et al, 2012) which has been shown to promote chondrogenesis amongst many other functions.…”
Section: Direct Administration Of Fgfmentioning
confidence: 99%